An Analyses The Growth And Adaptation Of Mangrove Seedlings Of Rhizophoraceae Family On Different Level Of Seawater Inundation To Support Mangrove Ecosystem Restoration Planning - Analuddin Analuddin; Andi Septiana; Jamili Jamili; Asrun Budiatma; Musdalifa Musdalifa; wiwin Wiwin; Sahidin Sahidin (Jurnal Perencanaan Wilayah, 2019)
The purposes of this study were to know the impact of different level of sea water inundation on the growth capacity and biochemical adaptation of the mangrove Rhizophoraceae family of Rhizophora mucronata and Bruguiera gymnorrhiza seedlings. The propagules of these mangroves were planted with different levels of sea water flooding, namely 90 cm, 60 cm, 45 cm and 30 cm. The growth of height and diameter of these mangrove seedlings were measured at early and termination of treatments, while their biochemical adaptations were analyzed in the Laboratory. The relatively growth rate RGR of high and diameter of these seedlings were analyzed, while statistical test was performed by anova. The RGR of high of the two mangrove seedlings were significantly different (P <0.05), though their RGR of diameter did not differ significantly (P> 0.05). The growth of height of R. mucronata seedlings was fastest at the lower level of inundation (30 cm) and the slowest at the higher level of submergence (90 cm). On the contrary, the height growth of B. gymnorrhiza seedlings was fastest at submergence of 90 cm, and the slowest at submergence of 30 cm. The flavonoids and vitamin C contents in both mangrove seedlings increased significantly (P <0.05) with increased inundation levels. Thus, although biochemical responses tended to be the same for both mangroves, but B. gymnorrhiza seedlings indicate  more able to grow and develop on rising sea levels than R. mucronata seedlings. This study provides important information for revegetation planning of degraded mangrove under a sea level rise scenario.Keywords: Biochemical adaptation, Sea water level, mangrove seedling growth, mangrove revegetation.